Chemoselective coupling reactions of 5,7-dimethoxyphthalide with the remotely functionalized alkyl iodides: facile racemic synthesis of helicobacter pylori antibiotics - Singh, Mandeep; N. P. Argade (Journal of Organic Chemistry, 2010)
Highly chemoselective coupling reactions of 5,7-dimethoxyphthalide carbanion with the remotely functionalized long chain alkyl iodides have been demonstrated to accomplish the concise and efficient synthesis of Helicobacter pylori antibiotics, the CJ-molecules, and sporotricale methyl ether.